Requirements Engineering: Foundation for Software Quality 29th International Working Conference, REFSQ 2023, Barcelona, Spain, April 17-20, 2023, Proceedings - Ferrari, Alessio; Penzenstadler, Birgit (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 29th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2023, which took place in Barcelona, Spain, during April 17-20, 2023. The 12 full technical design and scientific evaluation papers, 8 short research previews and vision papers, and 5 experience reports presented in this volume were carefully reviewed and selected from 78 submissions. They were organized in topical sections as follows: Requirements communication and conceptualization; NLP and machine learning for AI; RE for artificial intelligence; crowd RE; and RE in practice.
Requirements Communication and Conceptualization -- Requirements Engineering Issues Experienced by Software Practitioners: A Study on Stack Exchange -- An Empirical Study of the Intuitive Understanding of a Formal Pattern Language -- Supporting Shared Understanding in Asynchronous Communication Contexts -- Bringing Stakeholders Along for the Ride: Towards Supporting Intentional Decisions in Software Evolution -- Understanding the Role of Human-Related Factors in Security Requirements Elicitation -- Scope Determined (D) and Scope Determining (G) Requirements: A New Categorization of Functional Requirements -- NLP and Machine Learning for AI Using Language Models for Enhancing the Completeness of Natural-language Requirements -- Requirement or not, that is the question: A case from the railway industry 97 -- Summarization of Elicitation Conversations to Locate Requirements Relevant Information -- Ontology-based Automatic Reasoning and NLP for Tracing Software Requirements into Models with the OntoTrace Tool -- Requirements classi cation using fastText and BETO in Spanish documents -- RE for Artificial Intelligence -- Exploring Requirements for Software that Learns: A Research Preview -- Requirements Engineering for Automotive Perception Systems: an Interview Study -- An investigation of challenges encountered when specifying training data and runtime monitors for safety critical ML applications -- A Requirements Engineering Perspective to AI-based Systems Development: A Vision Paper -- Out-of-Distribution detection as Support for Autonomous Driving Safety Lifecycle -- Crowd RE -- Automatically Classifying Kano Model Factors in App Reviews -- Data-driven Persona Creation, Validation, and Evolution -- Towards a Cross-Country Analysis of Software-related Tweets -- Integrating Implicit Feedback into Crowd Requirements Engineering - a Research Preview -- RE in Practice -- Authoring, Analyzing, and Monitoring Requirements for a Lift-Plus-Cruise Aircraft -- Knowns and Unknowns: An Experience Report on Discovering Tacit Knowledge of Maritime Surveyors -- Feel It, Code It: Emotional Goal Modelling for Inclusive Design -- A Product Owner's Navigation in Power Imbalance Between Business and IT: An Experience Report -- Eliciting Security Requirements - an Experience Report.
Keywords: Software engineering; Education -- Data processing; Application software; Machine learning; Natural language processing (Computer science).; Software Engineering; Computers and Education; Computer and Information Systems Applications; Machine Learning; Natural Language Processing (NLP).